Writing 'new' decalogues: Martin Luther’s development of the Pauline-Augustinian tradition of natural law - Raath, A. (Koers, 2005)
This essay argues in favour of Martin Luther subscribing to the theory of natural law in his theology. An in-depth study of Luther’s views on natural law finds support for Brown’s thesis that Luther’s contribution to the tradition of natural law cannot be taken to form the basis of the theory of divine right prominent in the seventeenth century. Without venturing into the debate on natural law versus legal positivism, it is found that the perspective emanating from Luther’s natural law theory has an important political message for mankind as a whole in its implicit warning against positivistic and legalistic perspectives on law because these are apt to lead to confusion, relativism and historicism. Man, according to Luther’s view, therefore, has to revert to more fundamental principles (or values), representative of “ideal,” “good,” or “true,” norms for testing manmade law. The more specific implications of Luther’s views on natural law for Christians concern an eschatological vision of Christians’ involvement and work in God’s creation. This vision concerns man’s divine appointment to hold office and promote peace in society, and to contribute humbly towards God’s involvement in societies suffering from the effects of legalism or torn apart by conflict.